Effects of Immersive Virtual Reality-Based Movement Therapy on Upper ExtremityFunctions and Cognitive Functions in Stroke Patients - Demir, Oguzhan Bahadir; Gokbel, Tugba; Baydemir, Canan; Dursun, Erbil (Shahroud Journal of Medical Sciences, 2024)
Background: This controlled experimental study aimed to investigate the effect of immersive virtual reality-based movement therapy (IVRMT) on upper extremity functions (UEF), activities of daily living (ADL), and cognitive functions (CF) in chronic stroke patients. Methods: Patients who met the inclusion criteria, were randomly assigned to the study (IVR) or control groups. Both of the groups received 60 minutes/day of conventional rehabilitation program and occupational therapy and the IVR group received 30 minutes/day of additional IVR-MT for six weeks. UEF was evaluated by the Jebsen Taylor Hand Function Test (JTHFT), and the Box and Block Test (BBT), ADL was evaluated by the Barthel Index (BI), and 36-Item Short Form Survey (SF-36), and CF was evaluated with the Mini Mental Test (MMT). Results: There were no differences between the IVR (n=15), and control (n=10) groups for demographic and clinical characteristics or baseline results of JTHFT, BBT, BI, SF-36, and MMT. At six weeks post-treatment there were significant improvements in the IVR group in scores for moving large light cans (Pvalue=0.001) and moving large heavy cans (Pvalue=0.003) in the JTHFT, in BBT scores (Pvalue=0.004), in MMT (Pvalue=0.033) and for physical functioning (Pvalue=0.008) in the SF-36. In addition, the change in score in the IVR group for moving large light cans (Pvalue=0.008) and moving large heavy cans (Pvalue=0.002) at week 6 was significantly larger than in the control group. Conclusions: These results suggest that additional IVR-MT, in combination with conventional physiotherapy and occupational therapy might improve outcomes in UEF and CF in chronic stroke patients.